PERENCANAAN GEOMETRIK DAN TEBAL PERKERASAN KAKU JALAN TALANG PADANG TINGGI STA 0+200 – STA 8+400 KABUPATEN LAHAT SUMATERA SELATAN - Arif, Muhammad; Haula Lodiosi; Ibrahim; Kosim (PILAR, 2025)
The construction of Talang Padang Tinggi Road is one of the efforts to connect and optimize the movement of traffic both goods and people from the capital city of Lahat Regency to points of economic activity in the Pajar Bulan District, Jarai District, and surrounding areas that have potential for agribusiness and agro-industry without having to go through the Pagaralam City area. To plan the road geometrics, the appropriate regulations are used the Road Geometric Design Guidelines No.13/P/BM/2021. Rigid pavement planning used Road Pavement Design Manual No.02/M/BM/2017. The planning results of Talang Padang Tinggi Road STA 0+200 – STA 8+400 Lahat Regency are classified as class II Collector roads with a plan speed of 70 km/hour. On this road there are 8 bends including, 4 Full Circle bends and 4 Spiral Circle Spiral bends. This road section uses a rigid pavement layer with concrete quality of K-350 and layer thickness of 25 cm, while the foundation layer uses class A aggregate with a thickness of 15 cm. The total estimated cost incurred is IDR 80.001.619.000,00 (eighty billion one million six hundred nineteen thousand rupiah).